A Retrospective Longitudinal Study in a Cohort of Children With Dyskinetic Cerebral Palsy Treated With Tetrabenazine - Scalise, Roberta; Sgandurra, Giuseppina; Menici, Valentina; Capodagli, Nicola; Di Pietro, Roberta; Romeo, Domenico M.; Sini, Francesca; Pagliano, Emanuela; Foscan, Maria; Cioni, Giovanni; Battini, Roberta (Frontiers in Neurology, 2021)
Tetrabenazine has been studied with a variety of hyperkinetic movement disorders, but there is limited and empirical literature on the potential efficacy of tetrabenazine in children with dyskinetic cerebral palsy (DCP). The purpose of this study was to evaluate the efficacy of tetrabenazine in a sample of children with DCP using the Movement Disorders—Childhood Rating Scale 4–18 Revised (MD-CRS 4–18 R). The study is a multicenter retrospective longitudinal study in which the participants were selected from the databases of each Center involved, according to detailed inclusion criteria. The study was performed on 23 children and adolescents (19 male and 4 females; mean age 8.28 years, SD 3.59) with DCP having been evaluated before starting the treatment (baseline), after 6 and 12 months of treatment and in a sub-cohort after >2 years follow-up. A linear mixed model was used to evaluate the effects of the different timings on each MD-CRS 4–18 R Index (Index I, Index II, and Global Index) adding age and type of movement disorder as random effect. A significant clinical improvement related to a reduction of MD-CRS 4-18 R Indexes was detected between the baseline and after 6 and 12 months of treatment. Findings support the efficacy of tetrabenazine in children with DCP through a standardized outcome measure (MD-CRS 4–18 R) and confirm the use of this scale as a suitable tool to detect changes in further randomized clinical trials.